A multi-element ldh based on lithium ore and a preparation method and application thereof
Patent Information
- Application Number
- CN202611033709.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-13
AI Technical Summary
内蒙古锂矿石富含Li、Al、Mg等目标元素,若能通过可控工艺实现这些元素的协同活化、微量杂质深度去除与LDH结构构筑,可开发出低成本、高附加值的功能材料,解决锂矿石高值化利用与LDH制备成本高的双重难题,这是现有技术尚未实现的创新方向
1.资源效益:突破内蒙古锂云母型锂矿石“单一提锂”的传统模式,实现Li、Al、Mg等目标元素的协同高值化利用,同步高效去除微量杂质,显著提升矿产资源综合利用率与经济价值;
Smart Images

Figure CN122516977B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of inorganic functional material preparation and high-value utilization of mineral resources. Specifically, it relates to a multi-element LDH based on Inner Mongolia lithium ore and its preparation method, as well as the application of this material in the adsorption treatment of anion wastewater. Background Technology
[0002] Layered bimetallic hydroxides (LDHs) are a class of anionic functional materials with a unique two-dimensional layered structure. Due to the tunable metal ions in the layers and the exchangeable anions between the layers, they have irreplaceable application value in adsorption separation, heterogeneous catalysis, and energy storage. With the increasing demand for functional materials from related industries, the limitations of existing LDH preparation technologies are becoming increasingly apparent: on the one hand, raw materials mainly rely on chemically pure metal salts (such as LiCl, MgCl2, and AlCl3) or brine from salt lakes, resulting in high raw material costs, strong resource dependence, and significant geographical limitations; on the other hand, the development and utilization of lithium ore in Inner Mongolia mainly focuses on the extraction of single lithium salts (such as LiOH and Li2CO3), while the associated valuable elements such as Al and Mg in the ore are not effectively utilized, and small amounts of heavy metal impurities require additional treatment, which not only wastes resources but also increases process complexity and energy consumption.
[0003] In existing technologies, the synthesis of LDH is mostly limited to binary or ternary systems, resulting in severe homogenization of structure and properties. Furthermore, no technology has been developed to simultaneously achieve in-situ doping of Li / Al / Mg / F using Inner Mongolian lithium ore as raw material. Inner Mongolian lithium ore is rich in target elements such as Li, Al, and Mg. If these elements can be synergistically activated, trace impurities deeply removed, and LDH structures constructed through controllable processes, low-cost, high-value-added functional materials can be developed. This would solve the dual challenges of high-value utilization of lithium ore and high LDH production costs, representing an innovative direction that has not yet been realized in existing technologies. Summary of the Invention
[0004] One of the objectives of this invention is to provide a method for preparing multi-element LDH based on lithium ore, which has controllable process, thorough impurity removal and high resource utilization.
[0005] The second objective of this invention is to provide a multi-element LDH prepared by the above-described preparation method.
[0006] The third objective of this invention is to provide an application of the above-mentioned multi-element LDH in the adsorption treatment of anion wastewater.
[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a method for preparing a multi-element LDH based on lithium ore, comprising the following steps: (1) Roasting and activation: The lithium mica-type lithium ore from Inner Mongolia is crushed and then roasted and activated to obtain roasted ore; (2) Selective leaching: The roasted ore is mixed with a mixed acid and leached, then vacuum filtered to obtain Li-containing ore. + Al 3+ Mg 2+ Fe 3+ Ca 2+ (trace amount), F - The crude extract of the multi-component mixture; wherein the mixed acid is composed of hydrochloric acid with a concentration of 1~4 mol / L and hydrofluoric acid with a concentration of 0.5~2 mol / L at a volume ratio of 1:2~1:5; (3) Deep purification: Add ammonia to the crude leachate to adjust the pH to 4.0~5.0, so that Fe 3+ The calcium precipitate as hydroxide and is removed by filtration. Na₂CO₃ solution is added dropwise to the filtrate to adjust the pH to 6.5–7.5. After complete calcium precipitation, stirring is continued for 1–2 hours to remove residual trace amounts of calcium. 2+ After removing a small amount of silicic acid impurities, filter again. Add dilute hydrochloric acid dropwise to the filtered leachate to adjust the pH to 5.0-5.5. Stir at 40-50℃ for 1-2 hours to decompose and remove residual carbonate ions, thus obtaining the product containing Li. + Al 3+ Mg 2+ F - Multi-element leachate; (4) Regulation of metal ion ratio: Detection of Li in multi-component leachate + Mg 2+ Al 3+ The molar concentration is selectively supplemented with LiCl, MgCl2, or AlCl3 solution according to the preset metal ion ratio of LDH; wherein the preset metal ion molar ratio of LDH satisfies: Li / (Mg+Al)=0.05~0.2, Mg / Al=1~4; (5) Coprecipitation reaction: Heat the leachate to 70~95℃, add alkaline solution dropwise, and purge the reaction with nitrogen gas throughout to maintain the pH of the system at 9.0~10.5. Stir the reaction. The alkaline solution is an aqueous solution of NaOH with a concentration of 2~5 mol / L. (6) Crystallization treatment: The precursor suspension after co-precipitation is transferred to a hydrothermal reactor and crystallized at 100~160℃ for 8~24h; (7) Post-processing: The crystallized suspension is centrifuged, washed, and vacuum dried to obtain multi-element LDH.
[0008] The lithium ore in Inner Mongolia mainly consists of the following components by mass percentage: SiO2 55~65%, Al2O3 15~20%, Li2O 1.0~2.5%, MgO 3~6%, CaO 2.25~2.65%, Fe2O3 3~3.72%.
[0009] In some embodiments, in step (1), the particles are crushed to a particle size ≤ 0.1 mm; the calcination activation includes: heating to 550~750°C at a heating rate of 5°C / min and calcining at a constant temperature for 2~4 hours.
[0010] In some embodiments, the solid-liquid ratio of the roasted ore to the mixed acid in step (2) is 1:6 to 1:15 g / mL; In some embodiments, the leaching conditions in step (2) include: temperature 40~70℃, rotation speed 300~400r / min, and time 1~3h; In some embodiments, the vacuum degree of vacuum filtration in step (2) is 0.08~0.1MPa; In some embodiments, the concentration of ammonia in step (3) is 1~3 mol / L, and the concentration of Na2CO3 solution is 0.1~0.2 mol / L; In some embodiments, the dropping rate in step (5) is 2~5 mL / min; the stirring reaction rate is 400~500 r / min; and the stirring reaction time is 2~5 h.
[0011] In some embodiments, the centrifugation rate in step (7) is 8000~10000 r / min, the centrifugation time is 10~15 min, the vacuum drying temperature is 60~100℃, the vacuum degree is 0.09~0.1 MPa, and the vacuum drying time is 6~12 h.
[0012] Specifically, a method for preparing a specific multi-element LDH includes the following steps: 1. Ore pretreatment: (1) Calcination and activation: The lithium mica-type ore from Inner Mongolia is crushed to a particle size ≤0.1mm, placed in a muffle furnace, and heated to 550~750℃ at a heating rate of 5℃ / min. It is then calcined at a constant temperature for 2~4h and naturally cooled to room temperature. The calcination process destroys the aluminosilicate lattice structure in the ore, making Li + Al 3+ Mg 2+ Deintercalation from the crystal lattice, while simultaneously decomposing some fluorides to form free F. - This lays the foundation for subsequent leaching and impurity removal.
[0013] (2) Selective leaching: The roasted ore and mixed acid were added to the reactor at a solid-liquid ratio of 1:6 to 1:15 g / mL, and leached by stirring at 40 to 70°C and 300 to 400 r / min for 1 to 3 hours. After leaching, the solid residue was separated by vacuum filtration (vacuum degree 0.08 to 0.1 MPa) to remove most of the silicon impurities and obtain Li-containing ore. + Al 3+ Mg 2+ F - and a small amount of impurity ions (Fe) 3+ Ca 2+ The crude leachate of the mixture; wherein the mixed acid is a mixture of hydrochloric acid and hydrofluoric acid in a volume ratio of 1:2 to 1:5, wherein the concentration of hydrochloric acid is 1 to 4 mol / L and the concentration of hydrofluoric acid is 0.5 to 2 mol / L. (3) Deep impurity removal: Add ammonia to the crude leachate to adjust the pH to 4.0~5.0, and remove Fe by filtration. 3+ Add Na₂CO₃ solution dropwise to the obtained filtrate to adjust the pH to 6.5-7.5. After calcium precipitation is complete, continue stirring for 1-2 hours to remove residual trace amounts of Ca. 2+ After removing a small amount of silicic acid impurities, filter again. Add dilute hydrochloric acid dropwise to the filtered leachate to adjust the pH to 5.0–5.5. Stir at 40–50°C for 1–2 hours to decompose and remove residual carbonate ions, yielding a Li-containing product. + Al 3+ Mg 2+ F - The multi-element leachate.
[0014] (4) Regulation of metal ion ratio: Detection of Li in multi-component leachate + Mg 2+ Al 3+ Molar concentration, based on the metal ion ratio of the target LDH (Li / (Mg+Al) = 0.05~0.2, Mg / Al = 1~4, Li / (Mg+Al) represents Li + molar amount of Mg 2+ And Al 3+ The ratio of total molar amounts, Mg / Al represents Mg 2+ With Al 3+ (Molar ratio), selectively add chemically pure LiCl, MgCl2 or AlCl3 solution, stir for 30~60min until mixed evenly, adjust to the preset ratio and set aside.
[0015] 2. LDH synthesis: (5) Coprecipitation reaction: The multi-element leaching solution is transferred to a constant temperature water bath reactor and heated to 70~95℃. Nitrogen gas is introduced throughout the process for protection. Alkali solution is added dropwise at a rate of 2~5mL / min, while stirring at 400~500r / min. The pH of the reaction system is maintained at 9.0~10.5. After the addition is completed, stirring is continued at a constant temperature for 2~5h to form an LDH precursor suspension. The alkali solution is an aqueous solution of NaOH, wherein the concentration of the aqueous solution of NaOH is 2~5mol / L.
[0016] (6) Crystallization treatment: The precursor suspension is transferred to a hydrothermal reactor lined with polytetrafluoroethylene, with a filling degree of 70~80% (occupying the reactor volume), and crystallized at 100~160℃ for 8~24h. It is then naturally cooled to room temperature to promote the directional growth and structural improvement of LDH grains.
[0017] 3. Post-processing: (7) Centrifuge the crystallized suspension at 8000~10000r / min for 10~15min and collect the solid precipitate; wash the precipitate with deionized water until the washing liquid is neutral, and then vacuum dry it at 60~100℃ and 0.09~0.1MPa for 6~12h to obtain the multi-element LDH product.
[0018] Preferably, in step (1), the roasting temperature is preferably 600~700℃ and the roasting time is preferably 2.5~3h to ensure that the mineral structure is fully broken and that excessive sintering does not occur; Preferably, in step (2), the concentration of hydrochloric acid in the mixed acid is preferably 2~3 mol / L, the concentration of hydrofluoric acid is preferably 1~1.5 mol / L, the volume ratio of hydrochloric acid to hydrofluoric acid is preferably 1:3~1:4; the solid-liquid ratio is preferably 1:8~1:12 g / mL, the leaching temperature is preferably 50~60℃, and the leaching time is preferably 1.5~2.5h, taking into account both the leaching rate of the target metal and the removal effect of SiO2; Preferably, in step (3), the concentration of ammonia is 1~3 mol / L and the concentration of Na2CO3 solution is 0.1~0.2 mol / L; Preferably, in step (4), the metal ion ratio is Li / (Mg+Al)=0.2, Mg / Al=2~3, and the concentration of the supplemented LiCl, MgCl2 or AlCl3 solution is 1~2 mol / L to ensure uniform mixing and no new impurities are introduced. Preferably, in step (5), the concentration of NaOH in the alkaline solution is 3~4 mol / L; the dropping rate is preferably 3 mL / min; the reaction temperature is preferably 75~90℃; the pH is maintained at 9.5~10.5; and the reaction time is preferably 3~4 h to promote the uniform formation of LDH precursor. Preferably, in step (6), the crystallization temperature is preferably 120~150℃ and the crystallization time is preferably 12~18h to ensure the integrity of the LDH layered structure; Preferably, in step (7), the centrifugation speed is preferably 8500~9500 r / min, the centrifugation time is preferably 12 min; the drying temperature is preferably 80~90℃, and the drying time is preferably 8~10 h, to avoid damage to the product structure.
[0019] This invention uses lepidolite-type lithium ore from Inner Mongolia as raw material and achieves synergistic utilization of target elements and efficient removal of impurities through an integrated process route of "roasting activation - selective leaching - deep impurity removal - co-precipitation - crystallization". Its core mechanism is as follows: During mixed acid leaching, hydrochloric acid dominates Li + Al 3+ Mg 2+ The process involves leaching, where hydrofluoric acid reacts with SiO2 to form soluble fluorosilicic acid, achieving efficient separation of silicon from the target metal, removing most silicon impurities, and reducing the amount of F in the leachate. - Can be used with Al 3+ The formation of stable aluminum fluoride complexes broadens the stable pH range of aluminum, avoiding hydrolysis loss during deep impurity removal and ensuring the recovery rate of the target element. The deep impurity removal step uses a combination of pH-adjusted precipitation and filtration to simultaneously remove heavy metals and trace impurities, ensuring the purity of the leachate. The fluoride in the leachate... - Introduced through the roasting and decomposition of ore fluorides and the hydrofluoric acid leaching process, the concentration fluctuates within a small range under fixed leaching process parameters, allowing for stable participation in LDH interlayer intercalation without the need for additional precise control. The metal ion ratio control step ensures the required metal ion proportions for LDH layer formation by precisely supplementing LiCl, MgCl2, or AlCl3. In the co-precipitation reaction, the pH of the system is controlled by the alkali solution, enabling the synergistic precipitation of multiple target metal ions to form the LDH layer structure, with some F... - Entering the interlayer, with OH - By jointly balancing the positive charge of the layers and simultaneously regulating the interlayer spacing and surface charge distribution, the material's adsorption performance is optimized. The continuous introduction of nitrogen gas prevents the introduction of carbonate ions from the dissolution of CO2 in the air, thus reducing the impact of carbonate ions on F. - Competition in intercalation ensures the stability of material structure and performance. + Doping with F - Complexation can broaden the stable pH range of LDH, maintaining a pure phase layered structure within the range of 9.0 to 10.5 and avoiding the formation of magnesium hydroxide impurity phase; subsequent crystallization treatment promotes grain growth and channel formation, ultimately yielding high-purity multi-element doped LDH.
[0020] This preparation method, which combines "synergistic utilization of target elements + targeted removal of impurities + pore structure construction," offers the following core advantages: 1. Efficient resource utilization: Focusing on target elements such as Li, Al, and Mg in the ore, avoiding interference from trace impurities on product performance, and improving resource utilization efficiency; 2. Excellent product purity: Through a combination of impurity removal processes, heavy metals and trace impurities are deeply removed, ensuring the purity of the LDH structure and the stability of its performance; 3. Process integration and synergy: Simultaneously achieve impurity removal, element activation and structure construction, simplifying traditional process steps and reducing energy consumption and costs; 4. Structural performance optimization: Multi-metal doping and interlayer intercalation synergistically regulate the interlayer spacing and surface properties of LDH, improving mass transfer efficiency and active site utilization.
[0021] Secondly, the present invention provides a lithium ore-based multi-element LDH, which is prepared by the above-described preparation method.
[0022] This material uses LDH as the matrix, with Li, Al, and Mg multi-metal ions doped in the layers, and F introduced in situ in the interlayer. - , with OH - The positive charge of the common balancing layer is balanced, and it has a rich hierarchical channel structure; the material has a layered crystal phase-dominated structure, with fully exposed active sites and low impurity content.
[0023] Thirdly, the present invention provides an application of the above-mentioned lithium ore-based multi-element LDH in the adsorption treatment of anion wastewater.
[0024] Beneficial effects: 1. Resource benefits: Breaking through the traditional "single lithium extraction" model of lithium mica-type lithium ore in Inner Mongolia, it realizes the synergistic high-value utilization of target elements such as Li, Al, and Mg, and simultaneously and efficiently removes trace impurities, significantly improving the comprehensive utilization rate and economic value of mineral resources; 2. Performance advantages: The prepared multi-element doped LDH has high purity and unique structure. Compared with traditional LDH, it has better adsorption kinetics for organic anionic dyes and inorganic heavy metal anions, and can quickly remove anionic pollutants from water in a short time. 3. Process advantages: The preparation process is simple and controllable, the impurity removal steps are efficiently integrated, no expensive equipment and chemically pure reagents are required, energy consumption and costs are greatly reduced, and it is easy to scale up production.
[0025] The present invention has been described in detail above; however, the above embodiments are merely illustrative in nature and are not intended to limit the invention. Furthermore, this document is not limited to the foregoing prior art or the invention itself, or to any theory described in the following embodiments. Attached Figure Description
[0026] Figure 1 The XRD pattern of the multi-component LDH prepared in Example 1; Figure 2 SEM images of the multi-component LDH prepared in Example 1; Figure 3 EDS spectrum of the multi-component LDH prepared in Example 1; Figure 4 The graphs show the adsorption and removal rates of methyl orange for the examples and comparative examples. Detailed Implementation
[0027] The present invention will be further described below with reference to the embodiments. It should be noted that the following embodiments are provided for illustrative purposes only and do not constitute a limitation on the scope of protection of the present invention.
[0028] Unless otherwise specified, the raw materials, reagents, and methods used in the embodiments are all conventional raw materials, reagents, and methods in the art.
[0029] The lithium ore in this example comes from the Vilasto mining area in Keshiketeng Banner, Inner Mongolia Autonomous Region. It is a lithium mica ore. The results of its multi-element XRF chemical analysis are shown in Table 1 (content represents mass fraction).
[0030] Table 1
[0031] Example 1: Preparation of multi-component LDH 1. Calcination and activation: Crush the Inner Mongolia lepidolite-type lithium ore (composition as shown in Table 1) to a particle size ≤0.1mm, place it in a muffle furnace, raise the temperature to 650℃ at a heating rate of 5℃ / min, calcine at a constant temperature for 3h, and then cool it naturally to room temperature. 2. Selective leaching: Roasted ore and mixed acid (hydrochloric acid concentration 2.5mol / L, hydrofluoric acid concentration 1.2mol / L, volume ratio 1:3.5) were added to the reactor at a solid-liquid ratio of 1:10 (g / mL). The mixture was stirred and leached for 2 hours at 55℃ and 350r / min. The solid residue was separated by vacuum filtration (vacuum degree 0.09MPa) to obtain crude leachate. 3. Deep purification: Add 1 mol / L ammonia solution to the crude leachate to adjust the pH to 4.0-4.5, let it stand for 2 hours to precipitate, and then filter. Add 0.1 mol / L Na2CO3 solution to the filtrate to adjust the pH to 7.0. After the calcium precipitation is complete, continue stirring for 1.5 hours, let it stand, and then filter. Add 1 mol / L dilute hydrochloric acid to the filtered leachate to adjust the pH to 5.0-5.5, stir at 40-50℃ for 1-2 hours to decompose and remove residual carbonate ions.
[0032] 4. Metal ion ratio control: Detection of metal ion concentration (Li) in pure leachate. + 0.036 mol / L, Mg 2+ 0.00823 mol / L, Al 3+0.0741 mol / L) and F - With an ion concentration of 0.04 mol / L, add 1.5 mol / L MgCl2 solution (12 mL per 100 mL leachate) according to the molar ratio of Mg / Al=2.5 and Li / (Mg+Al)=0.2, and stir for 45 min until the mixture is homogeneous. 5. Coprecipitation reaction: Transfer the leachate to a constant temperature water bath reactor, heat to 85℃, and purge with nitrogen gas throughout the process. Add alkaline solution (NaOH concentration 3.5mol / L) dropwise at a rate of 3mL / min, maintain pH=10.0, and stir the reaction at 450r / min for 3.5h to form an LDH precursor suspension. 6. Crystallization treatment: The precursor suspension was transferred to a hydrothermal reactor with a filling degree of 75%, and crystallized at 135℃ for 15 hours, and then naturally cooled to room temperature. 7. Post-treatment: The crystallized suspension was centrifuged at 9000 r / min for 12 min, and the solid precipitate was collected; it was washed with deionized water until neutral, and then vacuum dried at 85℃ and 0.095 MPa for 9 h to obtain the multi-element doped LDH product.
[0033] XRD patterns of multi-doped LDH products, such as Figure 1 As shown, it displays typical layered structure characteristic peaks; the EDS spectrum is as follows. Figure 3 As shown, the element distribution is displayed; SEM is as follows. Figure 2 As shown, the layered morphology is displayed.
[0034] Example 2: Preparation of multi-component LDH 1. Calcination and activation: The lithium mica-type ore from Inner Mongolia (from the same batch as in Example 1, with similar composition) was crushed to a particle size of ≤0.1mm, heated to 580℃ at a heating rate of 5℃ / min, and calcined at a constant temperature for 3.5h, and then naturally cooled to room temperature; 2. Selective leaching: Roasted ore and mixed acid (hydrochloric acid concentration 1.8 mol / L, hydrofluoric acid concentration 0.9 mol / L, volume ratio 1:3) were added to the reactor at a solid-liquid ratio of 1:9 (g / mL). The mixture was stirred and leached for 2.5 h at 48℃ and 320 r / min. The solid residue was separated by vacuum filtration (vacuum degree 0.085 MPa) to obtain crude leachate. 3. Deep purification: Add 2 mol / L ammonia solution to the crude leachate to adjust the pH to 4.0-4.5, let it stand for 2 hours to precipitate, and then filter. Add 0.1 mol / L Na2CO3 solution to the filtrate to adjust the pH to 7.0. After the calcium precipitation is complete, continue stirring for 1.5 hours, let it stand, and then filter. Add 1 mol / L dilute hydrochloric acid to the filtered leachate to adjust the pH to 5.0-5.5, stir at 40-50℃ for 1-2 hours to decompose and remove residual carbonate ions.
[0035] 4. Metal ion ratio control: Detection of metal ion concentration (Li) in pure leachate. + 0.031 mol / L, Mg 2+ 0.0074 mol / L, Al 3+ 0.067 mol / L) and F - With an ion concentration of 0.03 mol / L, add 1.2 mol / L MgCl2 solution (11 mL per 100 mL leachate) according to the molar ratio of Mg / Al=2 and Li / (Mg+Al)=0.2, and stir for 30 min until the mixture is homogeneous. 5. Coprecipitation reaction: Transfer the leachate to a constant temperature water bath reactor, heat to 78℃, and purge with nitrogen throughout the process. Add alkaline solution (NaOH concentration 2.8mol / L) dropwise at a rate of 2.5mL / min, maintain pH=9.8, and stir for 4h to form an LDH precursor suspension. 6. Crystallization treatment: The precursor suspension was transferred to a hydrothermal reactor with a filling degree of 75%, and crystallized at 110℃ for 20 hours, and then naturally cooled to room temperature; 7. Post-processing: Centrifuge the crystallized suspension at 8800 r / min for 13 min, collect the solid precipitate; wash until neutral, and vacuum dry at 75℃ for 10 h to obtain the multi-element doped LDH product.
[0036] Comparative Example 1: Preparation of Li-Mg-Al ternary LDH using conventional chemical salts The difference from Example 1 is that Inner Mongolia lithium ore is not used as raw material. Instead, chemically pure LiCl, AlCl3, and MgCl2 are used as metal sources. They are mixed according to the target LDH metal ion ratio in Example 1 (i.e., Mg / Al=2.5, Li / (Mg+Al)=0.2) and directly subjected to co-precipitation, crystallization, and post-processing steps to obtain a traditional ternary Li-Mg-Al LDH sample.
[0037] Comparative Example 2: Preparation of LDH without deep impurity removal The difference from Example 1 is that step 3, the deep impurity removal step, is omitted; heavy metals are removed only by pH adjustment and precipitation. The remaining steps are the same, yielding a product containing trace amounts of Fe. 3+ Ca 2+ LDH samples containing impurities.
[0038] Comparative Example 3: Li-free Mg-Al-F ternary LDH The difference from Example 1 is that chemically pure AlCl3, MgCl2, and NaF are used as raw materials, and they are mixed in the same proportion as Al, Mg, and F in Example 1. The co-precipitation, crystallization, and post-treatment steps are carried out directly to obtain the Mg-Al-F ternary LDH sample.
[0039] Comparative Example 4: Preparation of Li-Mg-Al-F Quaternary LDH using Traditional Chemical Salts The difference from Example 1 is that chemically pure LiCl, AlCl3, MgCl2, and NaF were used as raw materials and mixed in the same proportion as Li, Al, Mg, and F in Example 1. The co-precipitation, crystallization, and post-treatment steps were directly performed to obtain a Li-Mg-Al-F quaternary LDH sample.
[0040] Test case The LDH samples from the examples and comparative examples were tested as follows: I. Adsorption experiment of large-radius anionic methyl orange: 1. Take a 100mL beaker and add 50mL of 20mg / L methyl orange solution; 2. Measure the pH of the solution with a pH meter, and adjust the pH to 7.0 ± 0.1 by adding 0.1 mol / L HCl or NaOH solution. 3. Accurately weigh 20.0 mg of LDH sample and add it to a beaker. At the same time, turn on the magnetic stirrer (300 r / min) and start timing immediately. 4. At 0, 5, 10, 15, 20, and 30 minutes, respectively, use a pipette to take 2 mL of sample and transfer it to a centrifuge tube; 5. Immediately place the centrifuge tubes into the centrifuge and centrifuge at 8000 rpm for 3 minutes; 6. Take the supernatant and measure the absorbance at a wavelength of 464 nm using a UV-Vis spectrophotometer, and record the data; 7. Repeat the above steps to test other samples in turn.
[0041] The results are shown in Table 2.
[0042] Table 2
[0043] Depend on Figure 4 It can be seen that Example 1 has the highest dye removal rate; compared with Comparative Example 1, Comparative Example 1 proves that F doping can improve adsorption performance; compared with Example 1, Comparative Example 4 proves that trace coexisting elements in the ore-source leaching solution can further optimize performance. Comparative Example 2 has the lowest removal rate (no impurity removal was performed), which is because without impurity removal, impurity ions will enter the interlayer and compete for adsorption sites; Comparative Example 3 has the second lowest removal rate, demonstrating the necessity of Li; Comparative Example 4 is a Li-Mg-Al-F system prepared with pure reagents in the same proportion, and its adsorption performance is lower than that of Example 1, proving that the synergistic effect of trace coexisting elements in the ore-source leaching solution can further optimize the material's adsorption performance.
[0044] The above results indicate that the adsorption kinetics of the multi-doped LDH prepared in this invention for methyl orange anionic dye are superior to those of conventional LDH and unpurified samples.
[0045] II. Adsorption experiment of potassium dichromate for small-radius inorganic anions: 1. Take a 100mL beaker and add 50mL of 20mg / L potassium dichromate solution; 2. Measure the pH of the solution with a pH meter, and adjust the pH to 7.0 ± 0.1 by adding 0.1 mol / L HCl or NaOH solution. 3. Accurately weigh 20.0 mg of LDH sample and add it to a beaker. At the same time, turn on the magnetic stirrer (300 r / min) and start timing immediately. 4. At 0, 5, 10, 15, 20, and 30 minutes, respectively, use a pipette to take 2 mL of sample and transfer it to a centrifuge tube; 5. Immediately place the centrifuge tubes into the centrifuge and centrifuge at 8000 rpm for 3 minutes; 6. Take the supernatant and measure the absorbance at a wavelength of 350 nm using a UV-Vis spectrophotometer, and record the data; 7. Repeat the above steps to test other samples in turn.
[0046] The results are shown in Table 3.
[0047] Table 3
[0048] Therefore, the multi-component doped LDH prepared by this invention has good adsorption performance for both organic anionic dyes and inorganic heavy metal anions. Compared with LDH prepared by traditional chemical salts, it has a better adsorption effect and can be applied to the synergistic treatment of multi-component anionic wastewater.
[0049] The above embodiments are merely illustrative of the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and substance defined by the claims of the present invention; and such modifications or substitutions are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing multi-element LDH based on lithium ore, characterized in that, Includes the following steps: (1) Roasting and activation: The lithium mica-type ore from Inner Mongolia is crushed and then roasted and activated to obtain roasted ore; the lithium ore includes the following components by mass percentage: SiO2 55~65%, Al2O3 15~20%, Li2O 1.0~2.5%, MgO 3~6%, CaO 2.25~2.65%, Fe2O3 3~3.72%; (2) Selective leaching: The roasted ore is mixed with a mixed acid and leached, then vacuum filtered to obtain Li-containing ore. + Al 3+ Mg 2+ Fe 3+ Ca 2+ F - The crude extract of the multi-component mixture; wherein the mixed acid is composed of hydrochloric acid with a concentration of 1~4 mol / L and hydrofluoric acid with a concentration of 0.5~2 mol / L at a volume ratio of 1:2~1:5; (3) Deep purification: Add ammonia to the crude leachate to adjust the pH to 4.0~5.0, so that Fe 3+ The calcium precipitate as hydroxide and is removed by filtration. Na₂CO₃ solution is added dropwise to the filtrate to adjust the pH to 6.5–7.
5. After complete precipitation, stirring is continued for 1–2 hours, followed by filtration to remove the precipitate again. Dilute hydrochloric acid is added dropwise to the filtered leachate to adjust the pH to 5.0–5.
5. The solution is stirred at 40–50°C for 1–2 hours to decompose and remove residual carbonate ions, yielding a solution containing Li. + Al 3+ Mg 2+ F - Multi-element leachate; (4) Regulation of metal ion ratio: Detection of Li in multi-component leachate + Mg 2+ Al 3+ The molar concentration is selectively supplemented with LiCl, MgCl2, or AlCl3 solution based on the preset metal ion ratio of LDH; wherein the preset metal ion molar ratio of LDH satisfies: Li + molar amount of Mg 2+ And Al 3+ The total molar ratio of Li / (Mg+Al) = 0.05~0.2, Mg 2+ With Al 3+ The molar ratio of Mg / Al is 1~4; (5) Coprecipitation reaction: The leaching solution is heated to 70~95℃, and an alkaline solution is added dropwise. Nitrogen gas is introduced throughout the reaction to maintain the pH of the system at 9.0~10.
5. The reaction is stirred to obtain a precursor suspension. The alkaline solution is a NaOH aqueous solution with a concentration of 2~5mol / L. (6) Crystallization treatment: The precursor suspension after co-precipitation is transferred to a hydrothermal reactor and crystallized at 100~160℃ for 8~24h; (7) Post-processing: The crystallized suspension is centrifuged, washed, and vacuum dried to obtain multi-element LDH.
2. The preparation method according to claim 1, characterized in that, In step (1), the particles are crushed to a particle size ≤ 0.1 mm; the calcination activation includes: heating to 550~750℃ at a heating rate of 5℃ / min and calcining at a constant temperature for 2~4 hours.
3. The preparation method according to claim 1, characterized in that, In step (2), the solid-liquid ratio of the roasted ore to the mixed acid is 1:6~1:15 g / mL.
4. The preparation method according to claim 1, characterized in that, The leaching conditions in step (2) include: temperature 40~70℃, rotation speed 300~400r / min, and time 1~3h.
5. The preparation method according to claim 1, characterized in that, The vacuum degree of vacuum filtration in step (2) is 0.08~0.1MPa.
6. The preparation method according to claim 1, characterized in that, In step (3), the concentration of ammonia water is 1~3 mol / L and the concentration of Na2CO3 solution is 0.1~0.2 mol / L.
7. The preparation method according to claim 1, characterized in that, In step (5), the dropping rate is 2~5 mL / min; the stirring reaction rate is 400~500 r / min; and the stirring reaction time is 2~5 h.
8. The preparation method according to claim 1, characterized in that, In step (7), the centrifugation rate is 8000~10000 r / min, the centrifugation time is 10~15 min, the vacuum drying temperature is 60~100℃, the vacuum degree is 0.09~0.1 MPa, and the vacuum drying time is 6~12 h.
9. A multi-element LDH based on lithium ore, characterized in that, It is prepared by any one of claims 1 to 8.
10. An application of the lithium ore-based multi-element LDH according to claim 9 in the adsorption treatment of anion wastewater.
Citation Information
Patent Citations
Preparation method for functional material for extracting lithium from aluminum salt
CA3215377A1
Process for preparing lithium carbonate by extracting lithium from lithium ore through wet method
CN117865190A